2017
DOI: 10.1016/j.jcp.2017.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the computation of the multivalued Painlevé transcendents on their Riemann surfaces

Abstract: We extend the numerical pole field solver (B. Fornberg and J.A.C. Weideman, J. Comput. Phys. 230:5957-5973, 2011) to enable the computation of the multivalued Painlevé transcendents, which are the solutions to the third, fifth and sixth Painlevé equations, on multiple sheets of their Riemann surfaces. We display, for the first time we believe, solutions to these equations on multiple Riemann sheets. We also provide numerical evidence for the existence of solutions to the sixth Painlevé equation that have pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Some recent numerical computations of Painlevé equations include: a pole field solver using Padé approximations [65,66,69,70,71,126,127]; numerical Riemann-Hilbert problems [119,120,122,121,133,142]; Fredholm determinants [26,27]; Padé approximations [110,112,144]; pole elimination [5,6,7,8,9,10,11]; a multidomain spectral method [96].…”
Section: Numerical Solution Of Painlevé Equationsmentioning
confidence: 99%
“…Some recent numerical computations of Painlevé equations include: a pole field solver using Padé approximations [65,66,69,70,71,126,127]; numerical Riemann-Hilbert problems [119,120,122,121,133,142]; Fredholm determinants [26,27]; Padé approximations [110,112,144]; pole elimination [5,6,7,8,9,10,11]; a multidomain spectral method [96].…”
Section: Numerical Solution Of Painlevé Equationsmentioning
confidence: 99%
“…If the large-z behavior of the solution is given by (2), then σ and B are no longer arbitrary but they become functions of λ and ν. Specifically, as demonstrated in [25], the connection formulae relating the large-z behavior, (2), and the small-z behavior, (9), are given by…”
Section: 2mentioning
confidence: 99%
“…Hence, the PFS enabled the study of unexplored P I , P II and P IV solutions, as reported in [11][12][13][32][33][34]. In [9], we extended the PFS method to the computation of multivalued solutions of the P III , P V and P VI equations, thus making the solution spaces of these equations amenable to numerical exploration. This paper is the first application of this enhanced PFS method to the survey of a class of multivalued Painlevé transcendents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we are interested in the tritronquée solutions in the regular sector and will construct them on unbounded lines via polynomial interpolation. If poles are to be studied, approaches based on Padé approximants as in [11,13,26] are to be used.…”
Section: Introductionmentioning
confidence: 99%